Produksi Seresah pada Tegakan Hutan di Blok Penelitian dan Pendidikan Taman Hutan Raya Wan Abdul Rachman Provinsi Lampung - Riyanto Riyanto; Indriyanto Indriyanto; Afif Bintoro (Jurnal Sylva Lestari, 2013)
Litter had an important function in a forest. The nutrients were derived from the litter is useful to improve the soil. The purposes of the research to determine the production of the litter, the analyse plants species and stands density, the correlation between litter production and stands density, the correlation between litter production and the number of plant species at research and educational block of Wan Abdul Rachman Great Forest Park. The research was conducted on October-December 2011 by using partition-line method. The litter was taken on a plot 1 m x 1 m in size systematically. The plants species found in the research area were avocado, palm, bisoro, cocoa, dadap, duku, durian, rubber, hazelnut, coffea, jackfruit, petai, betel nuts, rambutan, rosewood, and gnetum gnemon. The density of stands in research area dominated by cocoa trees. Based on the correlation analysis, forest stand density known influence the litter production. The high forest stand density increases litter production, whereas the correlation among litter production and the number of plant species is less influential, because not every plant able to fall out the leave easily. Keywords: forest stands, litter, research and educational block